Relación entre los niveles de Comprensión Lectora y las Actitudes hacia la Lectura en los estudiantes del 4° grado de Educación Primaria de la I.E “Rafael Narváez Cadenillas” y la I.E n° 81014 “Pedro Mercedes Ureña” – Trujillo, 2015 - Burgos Callisani, Maritza Judit (2017)
This study aims to identify the relationship between levels of reading comprehension and attitudes towards reading among students of 4th grade of primary education of the EI "Rafael Narvaez Cadenillas" and EI N° 81014 "Pedro Ureña Mercedes" – Trujillo, 2015. Descriptive correlational research was used. A sample of 156 students was used. For the reading comprehension level of students of institutions "Rafael Narvaez Cadenillas" and "Pedro Mercedes Ureña" Reading Comprehension Test was used. Moreover, a questionnaire to measure their attitudes toward reading among students in these educational institutions was implemented. Descriptive statistics were used to analyze the results of both tests, and inferential statistics to find the relationship between them._x000D_ The results showed that there is a positive and significant relationship between the varying levels of Reading and Reading attitudes towards the EI "Rafael Narvaez Cadenillas". The majority 58.8 % of students have a high level in relation to the Levels Reading Comprehension. In turn, 67.6 % have a high level in terms of attitudes toward reading._x000D_ Regarding EI N° 81014 "Mercedes Pedro Ureña" the results showed that there was a statistically significant relationship between levels of reading comprehension and attitudes toward reading of the students tested. The 43.2% have a high level in relation to the Levels Reading Comprehension. While 53.4 % of students have a high level regarding attitudes toward reading.